2021
DOI: 10.1002/pbc.29085
|View full text |Cite
|
Sign up to set email alerts
|

MYOD1 as a prognostic indicator in rhabdomyosarcoma

Abstract: Background/objectives: Rhabdomyosarcoma (RMS) is characterized by the expression of the myogenic regulatory protein MYOD1. Histologic types include alveolar, embryonal (ERMS), and spindle cell sclerosing RMS (SRMS). SRMS harbors MYOD1 mutations in a subset of adult cases in association with poor prognosis.Design/methods: To study the level of MYOD1 protein expression and its clinical significance, we have analyzed variable numbers of pediatric (<18 years of age) and adult (age range ≥18 to 35 years) ERMS and S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Recently, a lack of nuclear MYOD1 immunostaining in ERMS and spindle cell sclerosing RMS, that contrasts to the high level of staining associated with L122R mutations, has also been associated with inferior outcome, although numbers reported are so far small [92]. As MYOD1 is a key determinant of apparent differentiation status in RMS tumours, this lack of nuclear expression may reflect a relatively undifferentiated state.…”
Section: Mutations and Amplifications With Prognostic Impactmentioning
confidence: 99%
“…Recently, a lack of nuclear MYOD1 immunostaining in ERMS and spindle cell sclerosing RMS, that contrasts to the high level of staining associated with L122R mutations, has also been associated with inferior outcome, although numbers reported are so far small [92]. As MYOD1 is a key determinant of apparent differentiation status in RMS tumours, this lack of nuclear expression may reflect a relatively undifferentiated state.…”
Section: Mutations and Amplifications With Prognostic Impactmentioning
confidence: 99%
“…All these evidences support that TWIST1 is another potential driver gene in RMS. MYOD1 is a myogenic regulatory factor and is necessary for muscle fiber differentiation ( 61 ). However, its role in FN-RMS samples that we examined shows inconsistent results.…”
Section: Discussionmentioning
confidence: 99%
“…While in the St. Jude dataset, MYOD1 CN amplification is observed in FN-RMS, but no significant changes in term of gene expression between two fusion status subtypes. Zibat et al identified that MYOD1 is significantly lower expressed in FN-RMS (ERMS and FN-ARMS) than FN-RMS (PAX-FOXO1 ARMS) (62), and lacking of MYOD1 is associated with poor prognosis in ERMS (61). In addition, TWIST1 is a known MYOD1 inhibitor (63) and Tremblay et al have observed that YAP1 and TWIST1 could inhibit MYOD1 activity in ERMS (58).…”
Section: Rms Has Been Traditionally Classified Into Embryonal Rms ( E...mentioning
confidence: 99%
“…Diagnoses were confirmed by re-review of the histologic slides for the characteristic morphology and immunophenotype (Table 1). Patients and tumors were selected from our previous study [15] and were classified into three prognostic and histologic groups, based on clinical follow-up information and calculation of overall survival (Figure 1A). Group 1 was defined as tumors with adverse or poor prognosis and contained both ERMS and SRMS.…”
Section: Patients/subjects/samplesmentioning
confidence: 99%
“…Read-out of protein expression was estimated using signal to noise ratio (SNR) and quantified as 1-3 (SNR = 1 indicates protein signal similar to background noise; SNR = 3 indicates signal is three times the background noise). and tumors were selected from our previous study [15] and were classified into th prognostic and histologic groups, based on clinical follow-up information and calculat of overall survival (Figure 1A). Group 1 was defined as tumors with adverse or poor pr nosis and contained both ERMS and SRMS.…”
Section: Nanostring Digital Spatial Profilingmentioning
confidence: 99%